Prognostic validation and clinical implications of the EANO ESMO classification of leptomeningeal metastasis from solid tumors. Issue 7 (23rd December 2020) - Le Rhun, Emilie; Devos, Patrick; Weller, Johannes; Seystahl, Katharina; Mo, Francesca; Compter, Annette; Berghoff, Anna S; Jongen, Joost L M; Wolpert, Fabian; Rudà, Roberta; Brandsma, Dieta; van den Bent, Martin; et al.
Abstract: Background: The EANO ESMO guidelines have proposed a classification of leptomeningeal metastases (LM) from solid cancers based on clinical, magnetic resonance imaging (MRI), and cerebrospinal fluid (CSF) cytology presentation. MRI patterns are classified as linear, nodular, both, or neither. Type I LM is defined by positive CSF cytology (confirmed LM) whereas type II LM is defined by typical clinical and MRI signs (probable or possible LM). Here we explored the clinical utility of these LM subtypes. Patients and methods: We retrospectively assembled data from 254 patients with newly diagnosed LM from solid tumors. Survival curves were derived using the Kaplan–Meier method and compared by Log-rank test. Results: Median age at LM diagnosis was 56 years. Typical clinical LM features were noted in 225 patients (89%); 13 patients (5%) were clinically asymptomatic. Tumor cells in the CSF were observed in 186 patients (73%) whereas the CSF was equivocal in 24 patients (9.5%) and negative in 44 patients (17.5%). Patients with confirmed LM had inferior outcome compared with patients with probable or possible LM ( P = 0.006). Type I patients had inferior outcome than type II patients ( P = 0.002). Nodular disease on MRI was a negative prognostic factor in type II LM ( P = 0.014), but not in type I LM. On multivariate analysis, administration of either intrathecal pharmacotherapy ( P = 0.012) or systemic pharmacotherapy ( P = 0.0003) was associated with improved outcome in type I LM, but not in type II LM. Conclusion: The EANO ESMO LM subtypes are highly prognostic and should be considered for stratification and overall design of clinical trials.